2008
DOI: 10.1158/0008-5472.can-08-0343
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Caveolin-1 Regulates Rho/ROCK-Dependent Focal Adhesion Dynamics and Tumor Cell Migration and Invasion

Abstract: Rho/ROCK signaling and caveolin-1 (Cav1) are implicated in tumor cell migration and metastasis; however, the underlying molecular mechanisms remain poorly defined. Cav1 was found here to be an independent predictor of decreased survival in breast and rectal cancer and significantly associated with the presence of distant metastasis for colon cancer patients. Rho/ROCK signaling promotes tumor cell migration by regulating focal adhesion (FA) dynamics through tyrosine (Y14) phosphorylation of Cav1. Phosphorylated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
262
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 240 publications
(285 citation statements)
references
References 48 publications
16
262
1
2
Order By: Relevance
“…Further, c-Src-mediated caveolin-1 phosphorylation is reported to stimulate the subcellular trafficking of activated EGF-R augmenting cell migration and anchorage-independent growth [57][58][59]. To this end, Joshi et al [60] have recently shown phosphorylated caveolin-1 to co-operate with Rho/ROCK and FAK-dependent signalling pathways promoting tumour cell invasion and metastasis in breast cancer. Such studies are consistent with clinical data showing a positive correlation between caveolin-1 expression (although distinction between phosphorylated and nonphosphorylated forms not addressed) and poor patient survival in highly aggressive invasive breast cancers [42][43][44]61].…”
Section: Discussionmentioning
confidence: 99%
“…Further, c-Src-mediated caveolin-1 phosphorylation is reported to stimulate the subcellular trafficking of activated EGF-R augmenting cell migration and anchorage-independent growth [57][58][59]. To this end, Joshi et al [60] have recently shown phosphorylated caveolin-1 to co-operate with Rho/ROCK and FAK-dependent signalling pathways promoting tumour cell invasion and metastasis in breast cancer. Such studies are consistent with clinical data showing a positive correlation between caveolin-1 expression (although distinction between phosphorylated and nonphosphorylated forms not addressed) and poor patient survival in highly aggressive invasive breast cancers [42][43][44]61].…”
Section: Discussionmentioning
confidence: 99%
“…Control and KAI1-specific siRNA smart pools were transiently transfected in to MCF7 or HEK293 stable cell lines using Lipofectamine 2000 (Invitrogen) following the protocol described before (23). KAI1 knockdown was assessed by Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…MTT Assay-Cell proliferation assays were performed as described previously (23). Briefly, 10,000 cells were seeded on 96-well plates for 48 -72 h, prior to adding MTT reagent diluted 1:10 from 5 mg/ml stock in RPMI (MCF7; MDA-435) or Dulbecco's modified Eagle's medium (HEK293) medium, after which the cells were allowed to grow in a CO 2 incubator in the dark for 4 -5 h. The medium was decanted, precipitates of metabolite (Formazan) were dissolved in 200 l of Me 2 SO, and absorbance was measured at 570 nm.…”
Section: Volume 285 • Number 12 • March 19 2010mentioning
confidence: 99%
“…These results indicate that arachidonic acid-induced adhesion of MDA-MB-435 cells to type IV collagen requires both Rho activation and ROCK II signaling. Several proteins have been implicated as effectors of ROCK signaling, including myosin light chain (50), cofilin (51), and caveolin (52). We examined each of these in MDA-MB-435 cells and did not identify any ROCK-dependent changes in phosphorylation after treatment with arachidonic acid (data not shown), indicating that although Rho/ROCK is critical for the fatty acid-induced adhesion, the signaling apparently functions through other downstream effectors.…”
Section: Rock Is Necessary For Adhesion Of Mda-mb-435 Cells To Collagmentioning
confidence: 98%